2003
DOI: 10.1210/en.2002-0171
|View full text |Cite
|
Sign up to set email alerts
|

Weightlessness Induced Apoptosis in Normal Thyroid Cells and Papillary Thyroid Carcinoma Cells via Extrinsic and Intrinsic Pathways

Abstract: Apoptosis plays a pivotal role in development, tissue homeostasis, cancer, immune defense, and response to weightlessness. It can be initiated by external signals via death receptors, but may also emerge from mitochondria. We exposed mitochondria-rich thyroid carcinoma cells (ONCO-DG1 cell line) and normal thyroid cells (HTU-5) to conditions of simulated microgravity. After 24 h, 10% of the cancer cells had entered a Fas-dependent apoptotic pathway, but destruction and redistribution of mitochondria, microtubu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
67
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 40 publications
10
67
0
1
Order By: Relevance
“…This results in a failure of mitochondria transport along microtubules, followed by mitochondria clustering and alteration [29]. In accordance with other reports [27], we found an overexpression of Bax. This pro-apoptotic protein is responsible for pore formation in mitochondrial membranes [30].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This results in a failure of mitochondria transport along microtubules, followed by mitochondria clustering and alteration [29]. In accordance with other reports [27], we found an overexpression of Bax. This pro-apoptotic protein is responsible for pore formation in mitochondrial membranes [30].…”
Section: Discussionsupporting
confidence: 93%
“…The induction of apoptosis has been reported in different cell lines in simulated hypogravity [26,27]. It is established that cell exposure to both real and simulated hypogravity conditions causes cytoskeleton disorganization associated with microtubule disruption [28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cytoskeletal disorganization, mitochondrial damage occurred in a high percentage (about 40%) of the cells cultured in the RPM, as clearly appeared by analyzing the altered AF pattern, characterized by the disappearance of the intracellular organelles and formation of bluegreen fluorescent haloes due to the passage of intra-organelle content into the cytoplasm [Petit et al, 2001]. The overexpression of Bax observed in cells exposed to modeled hypogravity, in accordance with the findings of other authors [Kossmehl et al, 2003], further supports the involvement of the intrinsic pathway. Indeed, Bax is a pro-apoptotic factor responsible for pore formation in mitochondrial membranes [Gross et al, 1999].…”
Section: Discussionsupporting
confidence: 89%
“…In cells exposed to low g, enhanced expression of the death receptor Fas, activating the extrinsic pathway, was detected [Lewis et al, 1998;Grimm et al, 2002]. It was also found that hypogravity-induced apoptosis is accompanied by an alteration of the cytoskeleton, resulting in redistribution and then dissolution of the mitochondria [Schatten et al, 2001;Kossmehl et al, 2003], as occurs in the intrinsic mitochondrial-mediated cell death program [Shimizu et al, 2000].…”
Section: Discussionmentioning
confidence: 92%
“…Bcl-2 proteins localize or translocate to the mitochondrial membrane and modulate apoptosis by permeabilization of the inner and/or outer membrane, leading to the release of citochrome c or stabilization of the barrier function. Bcl-2 family members are altered in thyroid cancer (Kossmehl et al, 2003) and their levels are regulated by estrogen in some cell systems (Song and Santen, 2003). The antiapoptotic member Bcl-2 is up-regulated by E2 and by the ER agonist PPT, but downregulated by the ER agonist DPN in thyroid cancer cells, suggesting that ER induces Bcl-2 expression whereas ER reduces it (Zeng et al, 2007).…”
Section: Target Molecules Of Estrogen Receptors In the Thyroid Glandmentioning
confidence: 99%